Knowledge, Attitude and Practices Regarding Diarrhoea and Its Management among Mothers of Under Five Children at UHTC Vijayapura: A Cross Sectional Study - Patil, Santosh D; Bhovi, Ravindranath A (National Journal of Community Medicine, 2019)
Background: Children are our supreme asset and they are the future human resource of the country. Under five, a highly vulnerable group constitutes 13% of the total population in India. The objectives are to assess the knowledge and attitude of mothers of under five children regarding diarrhea and to know the practice of mothers of under five children regarding management of diarrhea. Methods: A cross-sectional study was carried out during June 2018-Navember 2018. A structured and pre-tested questionnaire was administered to all the mothers of under-five children in the study area. Results: Of the 160 mother’s majority were in the age group of 21-25yrs. The diarrhoeal prevalence was 38 %. 64 % could define diarrhoea correctly and 94.7% of them had heard of ORS.89.76% of mothers sought treatment from private doctors when their children suffered from diarrhoea. Conclusions: Lack of education in mothers was found to be an obstructing factor for the appropriate utilization of ORS in the community. Although awareness regarding spread of diarrhoea and ORS was adequate in this community, knowledge regarding continuation of feeding and danger signs was deficient.